OPTIMIZING SOLAR OUTPUT TO REDUCE PHOTOVOLTAIC PANEL NUMBER IN IRRIGATION - Zeinaldeen, Laith. A. Zeinaldeen; Reeve, John. D. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This experiment aimed to study the effect of integrating a passive cooling system with varying air passage outlet clearances: 0 cm (C0, control), 10 cm (C1), 15 cm (C2), and 20 cm (C3) on the performance of polycrystalline and monocrystalline PV panels used in solar-powered irrigation systems. Performance metrics included PV efficiency, maximum power, required number of panels, and operational costs. Results showed a highly significant effect (P < 0.0001) of air passage clearance and PV type on all measured parameters. Specifically, the 10 cm clearance (C1) yielded the best outcomes, achieving the highest PV efficiency (16.26%), maximum power (41.12 W), lowest panel number (7), and lowest operational cost (8.75). Among panel types, polycrystalline panels demonstrated superior efficiency (12.52%), maximum power (32.05 W), required fewer panels (11), and incurred lower operational costs (13.50) compared to monocrystalline panels. These findings indicate that optimizing passive cooling can significantly enhance PV performance while reducing system size and costs.